Energy-Aware Elastic Multi Controller Based SDN Control Plane for Efficient Load Balancing - E. Sivarajan
Software-defined networking (SDN) approach makes network management decisions independent of the control and data layers. Several controllers can manage various network segments to guarantee reliable and efficient operation due to the distributed SDN architecture, which efficiently handles contemporary SDN systems. Nevertheless, higher-load controllers are always explicitly regarded as overloaded controllers in distributed SDN, meaning that their load must be shifted to other controllers to prevent energy consumption and network latency. In this paper, a novel Pelican Optimized Taylor series-based SDN load balancer (POT-SDN) algorithm is proposed, which reduces energy consumption and delay and improves the performance of multicore processors. The proposed POT-SDN method uses a novel Pelican Optimized Taylor series (POT) algorithm for performing switch migration and balances the load efficiently. The efficacy of the developed POT-SDN method has been assessed using specific parameters such as energy consumption, Packet Loss Ratio (PLR), ARU, throughput, migration cost utilization and response time. Simulation findings demonstrate that POT-SDN network works better than current methods by reducing the Load Balancing (LB) controller time by about 87%, lowering the packet loss ratio by 49%, and raising the average throughput by 23%.